Contributions of family caregivers to the coordination of services for the frail elderly - Lortie, Maude (Igitur, Utrecht Publishing & Archiving, 2009)
PURPOSE: This presentation concerns the contribution of family caregivers to the coordination of services for the frail elderly. THEORY: The role of family caregivers is partly conditioned by the conjuncture of health and social care organization. In recent years, many efforts were devoted to the creation of services integration devices which aim to improve user experience in particularly fragmented services organization [1]. In this context, family caregivers increasingly draw from their personal resources to care for their loved ones. In fact, Ducharme and colleagues [2] estimated that 80% of the care received is dispensed by family caregivers. Therefore, a better understanding of the contribution of family caregivers to coordinated care was deemed pertinent. METHODS: Our exploratory study consisted of 12 interviews with family caregivers and frail elderly users concerning their coordination experience. RESULTS AND CONCLUSIONS: In all circumstances, family caregivers have an important contribution to coordination. In fact, they absorb the coordination surplus required during the pre-installation phase of case management or during the users' episodes of transforming needs. This reveals a temporal gap between the need for coordination and the effective deployment of case management. Therefore, they appear as the primary bearers of services coordination.